(untitled) (Eureka Journal of Humanities and Social Research, 2026)
In modern Karakalpak literary criticism, studying a writer’s craftsmanship through artistic means of expression is considered one of the key factors defining the poetics of prose. The article provides a scientific analysis of the specific use of tropes such as simile, metaphor, metonymy, and synecdoche in Sh. Seytov’s novel "Aktuba in Jamanshyganak." Using methods of textual analysis and stylistic comparison, the role of artistic devices in revealing character traits and enhancing the emotional impact of the work is substantiated. As a result, it is established that the writer’s skillful use of the figurative potential of the folk language forms the basis of his individual authorial style. This research serves as a scientific foundation for a deeper study of Sh. Seytov’s literary heritage and the poetics of the Karakalpak novel.